Perancangan Game Edukasi Seni Budaya "Artsia" sebagai Multimedia Interaktif untuk Siswa Kelas VII di SMPN 2 Purwakarta Menggunakan Aplikasi Unity - Putri Alina Sidik, Legira; Widodo, Suprih; Wachid Abdul Majid, Nuur; Aulia Sodikin, Reisa (Journal of Information System and Education Development, 2025)
This article uses Unity software to discuss the design of the educational game "Artsia" as an interactive multimedia tool for seventh-grade students at SMPN 2 Purwakarta. The integration of arts education into the curriculum is crucial in the era of globalization, helping students appreciate cultural diversity and enhancing creativity. However, challenges such as limited teaching resources and abstract concepts in art education hinder effective learning. To address these issues, "Artsia" was developed as an interactive learning media, combining video, quizzes, and games to engage students actively. The research employs a literature review and Research and Development (R&D) methodology, including the DDD-E model for design and evaluation. The outcome is an accessible mobile application that supports independent learning, aiming to motivate students and improve their understanding of art concepts.